Pengaruh Pendidikan Kesehatan Tentang Deteksi Dini Kanker Payudara dengan SADARI Terhadap Pengetahuan Remaja Putri - Ningsih, Nurna; Permata Sari, Yulia Indah; Girsang, Bina Melvia (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Backrgound: Breast cancer is the second cause of death on women. Therefore, one method is needed to detect breast cancer earlier, one of that is by breast-self examination (BSE). Aims: The aim of this study is to determine the effect of health education on BSE on knowledge of teens. Methods: This study was used pre-post experimental test design without control group. The population in this study was the teens in 11th grade on senior high school of North Indralaya with sample of 35 teens. Analysis of experimental data used paired t-test. Results: The results showed the average knowledge of the teens has increased from 12.20 (pretest) to 14.57 (posttest) with p-value of 0.000 (